Dreaming in Bipolar Disorders – Feasibility of the Central Image Method: A Prospective Controlled Trial - Schmid-Mühlbauer, Gabriele; Reggiannini, Laura; Treu, Peter; Chae, Woo Ri; Stamm, Thomas (Frontiers in Psychology, 2024)
Background: Emotions play an important role in the emergence, formation and experience of dreams. The Central Image (CI) in a dream refers to the dream's dominant or underlying emotion, and it is the best-remembered part of a dream. Bipolar disorders are characterized by strong emotions, particularly during manic and depressive episodes. In these patients, dreams and CIs may serve as a helpful diagnostic and therapeutic tool. The aims of this study are to evaluate the feasibility of the CI Method and to check for differences concerning dreams and CI emotions between healthy controls and patients with bipolar disorder.Methods: Over a period of three weeks, 61 participants were asked to maintain a daily record of all dreams remembered. Dream reports were rated using the Cental Image Method (CIM) by two independent, blinded raters. We assessed for interrater agreement on the CIM, and for within and between group differences related to negative and positive CI emotions.Results: Mean agreement rates (weighted Cohen's Kappa) for the CI emotion ratings could be classified as very good: For primary CI emotion ratings, mean weighted Cohen's Kappa was 0.99 (± 0.02), and for secondary CI emotions 0.90 (± 0.17). Regarding the CI intensities, the mean agreement rate (Spearman's correlation) was also strong. Evaluation of differences within the groups showed that there were more negative compared to positive CI emotions in healthy controls and currently depressive patients; however, in the latter the difference was statistically not significant. Analyses of differences between groups indicated that patients who were currently depressed recorded more negative CI emotions in dreams than those who were euthymic, or healthy controls.The findings support the feasibility of the CIM. Our results might indicate different emotion regulation and defence mechanisms across bipolar disorder states, as reflected by the occurrence of negative and positive CI emotions.